2019
DOI: 10.1122/1.5063796
|View full text |Cite
|
Sign up to set email alerts
|

The yield normal stress

Abstract: Normal stresses in complex fluids lead to new flow phenomena because they can be comparable to or even larger than the shear stress itself. In addition, they are of paramount importance for formulating and testing constitutive equations for predicting non-viscometric flow behavior. Very little attention has so far been paid to the normal stresses of yield stress fluids, which are difficult to measure. We report the first systematic study of the first and second normal stress differences, N1 (>0) and N2 (<0), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 32 publications
5
47
0
Order By: Relevance
“…They found the ratio of the yield stress measured in uniaxial elongation to its value measured in shear flow to be greater, by a factor of 1.5, than the value predicted by the ideal viscoplastic theory. Moreover, de Cagny et al (7) combined steady and oscillatory measurements of normal stresses in shear flows of EVP materials. They found that the first normal stress difference developed in shear flow is positive, that the second normal stress difference is negative, and that both are comparable in magnitude to the shear stress.…”
mentioning
confidence: 99%
“…They found the ratio of the yield stress measured in uniaxial elongation to its value measured in shear flow to be greater, by a factor of 1.5, than the value predicted by the ideal viscoplastic theory. Moreover, de Cagny et al (7) combined steady and oscillatory measurements of normal stresses in shear flows of EVP materials. They found that the first normal stress difference developed in shear flow is positive, that the second normal stress difference is negative, and that both are comparable in magnitude to the shear stress.…”
mentioning
confidence: 99%
“…The behaviour of the first normal stress difference, N 1 , (Fig. 3a, inset) is different from that expected of fibrillar dispersions, for which N 1 would typically increase with γ̇ due to fibrous aggregates becoming elongated in the direction of the applied shear [52][53][54] . Here, N 1 decreased with γ̇ (for γ̇ > ~ 0.05 s -1 ), indicating that the aggregates became shorter in the direction of the applied shear.…”
Section: Solventmentioning
confidence: 72%
“…In the present study, the normal yield stress [25] and the yield stress tensor [26] were approximated by measuring only the static shear yield stress ( ). We then assumed that the measured was close to normal yield stress.…”
Section: Rheological Characterisation Of Silicone Elastomer Formulationsmentioning
confidence: 99%